2011
DOI: 10.1001/archgenpsychiatry.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Linking an Anxiety-Related Personality Trait to Brain White Matter Microstructure

Abstract: Increased HA is associated with decreased WM microstructure, implying that structural connectivity modulates anxiety-related aspects of personality. Decreased WM integrity reflects increased susceptibility to psychiatric disease and represents a promising biomarker that might ultimately facilitate targeted pharmacological and psychological interventions and treatment of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 81 publications
13
90
2
Order By: Relevance
“…RD, NS and P were positively correlated with the striatal-frontal fiber connectivity and HA was positively correlated with the striatal-hippocampal fiber connectivity (Cohen et al, 2009). Integrity of white matter microstructure in pathways connecting hubs of the corticolimbic circuit was also correlated with HA (Westlye et al, 2011). Voxel-based morphometric studies provided further support for the involvement of subcortical regions (the amygdala, striatum, and hippocampus) and the frontal cortex in temperaments (Gardini et al, 2009;Iidaka et al, 2006;Van Schuerbeek et al, 2011;Yamasue et al, 2008b).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…RD, NS and P were positively correlated with the striatal-frontal fiber connectivity and HA was positively correlated with the striatal-hippocampal fiber connectivity (Cohen et al, 2009). Integrity of white matter microstructure in pathways connecting hubs of the corticolimbic circuit was also correlated with HA (Westlye et al, 2011). Voxel-based morphometric studies provided further support for the involvement of subcortical regions (the amygdala, striatum, and hippocampus) and the frontal cortex in temperaments (Gardini et al, 2009;Iidaka et al, 2006;Van Schuerbeek et al, 2011;Yamasue et al, 2008b).…”
Section: Introductionmentioning
confidence: 73%
“…The significant role of the striatal-frontal pathway in HA can be easily integrated with previous research. A recent study found that increased HA was associated with decreased fractional anisotropy and increased mean and radial diffusivity in major fiber tracts, such as anterior thalamic radiation, dorsal cingulum bundle, inferior longitudinal fasciculus, superior longitudinal fasciculus, and uncinate fasciculus, which underlie pathways connecting critical hubs in the limbic-cortical and striatal-frontal circuits including the mOFC, dlPFC, PCC, ACC, amygdala, striatum and so on (Westlye et al, 2011). Structural integrity of white matter indexed by fractional anisotropy in a pathway connecting the amygdala, ventral striatum, and frontal cortex was also inversely correlated with anxiety, a trait closely correlated with HA (Kim and Whalen, 2009).…”
Section: Harm Avoidancementioning
confidence: 99%
See 2 more Smart Citations
“…Low HA has been associated with risk-taking, harmful behavior, impulsiveness, suicidal ideation, and aggression (Cloninger, 1986;Peirson, Heuchert, Thomala, Berk, Plein, & Cloninger, 1999), whilst high HA has been associated with behavioral inhibition, anxiety and neuroticism (Carver & Miller, 2006). HA is referred to as the anxietyrelated personality dimension (Montag, Reuter, Jurkiewicz, Markett, & Panksepp, 2013), and therefore high HA levels are tightly associated with neurobiological pathologies such as depression and anxiety (Arnold, Zai, & Richter, 2004;Commons, Connolley, & Valentino, 2003;Kenna, RoderHanna, Leggio, Zywiak, Clifford, Edwards, & Swift, 2012;Westlye, Bjornebekk, Grydeland, Fjell, & Walhovd, 2011).…”
Section: Robertmentioning
confidence: 99%